POTENTIAL AQUIFER RECHARGE DETERMINATION FOR COSTA RICA’S COLD RIVER BASIN USING A GEOGRAPHIC INFORMATION SYSTEM - Ramírez-Granados, Pablo (Revista Geográfica de América Central., 2014)
In hydrogeology and water resources management, one of the priority areas of research involves studies of aquifer recharge from rainfall. These studies generally involve several methodologies, one being the implementation of water balance. In recent years, with the rise of geographic information systems in hydrogeological studies, ease of integration, management, consulting and modeling of geodata has allowed more accurate quantifying and modeling of groundwater. This article shows the potential aquifer recharge in the Río Frío (Cold River) Basin through the implementation of a soil-water balance from a series of geohydrological variables. Modeling of geodata in the geographic information system included spatial interpolation methods and map algebra. The information used for the construction modeled water balance to identify areas of potential aquifer recharge from rainfall.